MAINTAINING JAVANESE LANGUAGE THROUGH JAVANESE TRADITIONAL FOOD NAMES IN DHOPLANG CULTURAL TOURISM SITE - Wiwiek Sundari (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
Language, both spoken and written, whether it is alive or dead, will becontinuously preservedby linguist and historian as an evidence of human being civilization as it is used as medium of knowing the culture of its users. Through language in prescription onoral story, a culture is shared. Thus, when a language extinct after its speakers weregone so that they cannot passing it intotheir future users or after their descendantsshifttheir language into another more beneficial languages than theirs so that the previous one isno longer used,a culture is also dead as it only written and not used. To preserve the language, language maintenance is needed. One of the ways to do it is by using it in tourism site to let people aware of their own language and culture as well as to introduce it into public. This research showshow Javaneselanguage is integrated in Dhoplang Javanese Traditional Market in Wonogiri, Central Java as it sells Javanese traditional foodusing Javanese traditional wrapping made of banana leaves. The management is also ordering buyers and requesting sellers to use Javanese language and wear Javanese traditional clothes. The result shows that thetourism site remindssellers and buyers of their language and introduce the language it into people who are not Javanese since they know what the meaning and philosophy of the food names andwrappingthatserves as the language preservation.Keywords:Javanese language and culture maintenance, Dhoplang, food and food wrapping names